Effect of Cadmium and Vitamin C on Citrobacter Freundii's Antioxidant Enzymes and Stress Markers - İbrahim, Muhammad Salihu; Çakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2022)
In this study, Citrobacter freundii (NRRL B-2643) bacteria were grown in LB medium containing varying concentrations of cadmium (Cd). In order to reduce the negative effect of Cd, different concentrations of vitamin C, known for its antioxidant properties, were added to the Cd-containing growth medium. Bacterial concentration, soluble protein and activities of antioxidant enzymes (Glutathione peroxidase (GSH-Px), Glutathione reductase (GSH-Rd), Superoxide dismutase (SOD), Catalase (CAT) and peroxidase (POD)) were determined by spectrophotometer. In addition, reduced and oxidized glutathione (GSH and GSSG), 4-hydroxyneoneal (4-HNE), malondialdehyde (MDA) amounts were determined by HPLC. No significant microorganism growth was observed at 150 ppm and higher Cd concentrations. Bacteria production was not affected up to 40 ppm Cd concentration. Bacteria were grown in media containing 0, 75, 100 and 125 ppm Cd. The protein content of the microorganism grown in the medium containing 75, 100 and 125 ppm Cd decreased about 24, 44 and 62 percent, respectively, comparisons to the control. When 50 ppm of vitamin C was added to the same growth medium, the percentage decrease in protein amount compared to the control was found to be 10, 31 and 50, respectively. An increase was observed in the antioxidant enzymes activities and stress markers in bacteria grown in cadmium-containing media compared to the control (p<0.05). With the addition of 25, 50 and 75 ppm vitamin C to cadmium-containing media, a decrease was observed in the activities of antioxidant enzymes and the amounts of stress markers.
Keywords: Citrobacter freundii; Antioxidant Enzymes